“Et in Utopia ego”: Sir Thomas More and “Montesinos,” a Southey Mystery “Solved” - Duggett, Tom (Romanticism on the Net)

(untitled) (Université de Montréal, 2017)
This essay sets out to solve the strange case of the “disappearance” of the Poet Laureate, Robert Southey, in his own 1829 book of “imaginary conversations” or Colloquies with the ghost of Sir Thomas More. There is no “Southey” in the dialogue, only a figure named “Montesinos.” But since the pessimistic ghost of More evidently speaks for Southey—as readers from the Westminster Review in summer 1829 onwards have noticed—then the dialogue is strangely one-sided. If More is Southey, then “who,” as Mark Storey’s biography asks, “is Montesinos?” This essay seeks to answer Storey’s biographical question, and to put it into the wider context of Southey’s ideas about national and writerly identity, and his Romantic poetics of history. The first part explores “Montesinos” as a byword for Southey’s literary utopianism. The second part then attempts the resurrection of “Montesinos,” tracing this figure in the detail of Southey’s “Hispanist” reading and in the workings of his historical imagination. I conclude with reflections on the implications of Southey’s ‘hieroglyphic’ mode of life-writing for historicist approaches to Romantic studies today, including the ‘new counterfactualism’ and the ‘speculative revivals’ of ‘Romantic biography’.